New perspectives on mixed languages from core to fringe - Mazzoli, Maria; Sippola, Eeva (Language contact and bilingualism ;, 2021)
This series offers a wide forum for work on contact linguistics, using an integrated approach to both diachronic and synchronic manifestations of contact, ranging from social and individual aspects to structural-typological issues. Topics covered by the series include child and adult bilingualism and multilingualism, contact languages, borrowing and contact-induced typological change, code switching in conversation, societal multilingualism, bilingual language processing, and various other topics related to language contact. The series does not have a fixed theoretical orientation, and include.